Dielectric and Electromagnetic Attenuated Properties of WC/Wax Composite - Yang, Weiming; Sun, Mengxiao; Yang, Zhiqian; Xu, Chang; Xia, Yilu; Xiong, Ziming (Frontiers in Materials, 2020)
In this study, tungsten carbide (WC) microparticles with different sizes were synthesized by the heating-programmed temperature method. Tungsten carbide produces obvious resonance peaks at intermediate and high frequencies, which contribute to electromagnetic absorption performance. The results show that a composite consisting of 30 vol.% WC exhibits a strongest absorption point (RLmin) of −71.81 dB, when the thickness is only 1.89 mm.